4. Simplify: \( \left(\frac{2 x^{3} y^{2}}{x^{2}}\right)^{-2} \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Beyond the Answer
To simplify \( \left(\frac{2 x^{3} y^{2}}{x^{2}}\right)^{-2} \), we start by simplifying the fraction inside the parentheses: 1. Simplifying the fraction: \[ \frac{2 x^{3} y^{2}}{x^{2}} = 2 x^{3-2} y^{2} = 2 x^{1} y^{2} = 2xy^{2} \] 2. Now substituting back into the expression: \[ \left(2xy^{2}\right)^{-2} \] 3. Applying the exponent: \[ \left(2xy^{2}\right)^{-2} = \frac{1}{(2xy^{2})^{2}} = \frac{1}{2^{2} (x)^{2} (y^{2})^{2}} = \frac{1}{4x^{2}y^{4}} \] Thus, the simplified expression is \(\frac{1}{4x^{2}y^{4}}\).